DEM study of the size-induced segregation dynamics of a ternary-size granular mixture in the rolling-regime rotating drum - Yang, Shiliang (2019)
Segregation induced by size, shape, or density difference of the granular material is inevitable in both natural and industrial processes; unfortunately, the underlying mechanism is still not fully understood. In view of the ubiquitous continuous particle size distributions, this study builds on the considerable knowledge gained so far from binary-size mixtures and extends it to a ternary-size mixture to understand the impact of the presence of a third particle size in the three-dimensional rotating drum operating in the rolling flow regime. The discrete element method is employed. The evolution of segregation, the active-passive interface, and the dynamical response of the particle-scale characteristics of the different particle types in the two regions are investigated. The results reveal that the medium particles are spatially sandwiched in between the large and small particles in both the radial and axial directions and therefore exhibit behaviors intermediate to the other two particle types. Compared to the binary-size mixture, the presence of the medium particles leads to (i) higher purity of small particles in the innermost of the radial core, causing a decrease of the translational velocity of small particles; (ii) decrease and increase of the collision forces exerted on, respectively, the large and small particles in both regions; and (iii) increase in the relative ratio of the active-passive exchange rates of small to large particles. The results obtained in the current study therefore provide valuable insights regarding the size-segregation dynamics of granular mixtures with constituents of different sizes.